Preparation process of magnesium phosphate cement-based synchronous grouting material for seabed shield tunnel

By using magnesium phosphate cement-based materials in the construction of subsea tunnels, combined with materials such as active metakaolin and activated fly ash, the problems of long settling time and low early strength of traditional synchronous grouting materials are solved, and the rapid hardness and early strength of grouting materials are improved, and the structural strength and service safety of subsea tunnels are improved.

CN119613078AActive Publication Date: 2025-03-14SHANDONG UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202410595900.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-05-13
Filing Date
2024-05-14
Publication Date
2025-03-14
Estimated Expiration
2044-05-14

AI Technical Summary

Technical Problem

Traditional synchronous grouting materials have problems such as long settling time, low early strength, and susceptible to seawater erosion in the construction of subsea tunnels, resulting in reduced tunnel structure strength and threatened service safety.

Method used

Magnesium phosphate cement-based material is used as the main gelling component, and active metakaolin clay is formed by mixing metakaolin with Mg2+ containing solution and adding alkali solution for calcination. At the same time, waste incineration fly ash and phosphoric acid are used to pretreat it to form active fly ash, and combined with materials such as refired magnesium oxide powder and fly ash to form alkaline and acidic components. Finally, magnesium phosphate cement-based synchronous grouting material is formed by mixing these components.

Benefits of technology

It achieves fast hardness and early strength of grouting materials, excellent anti-seepage performance, good slurry stability, and can effectively improve the structural strength and service safety of the subsea tunnel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613078A_ABST
    Figure CN119613078A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of cement-based material preparation, and particularly discloses a preparation process of a seabed shield tunnel magnesium phosphate cement-based synchronous grouting material, which comprises the following steps: (1) uniformly mixing metakaolin and a Mg < 2 + >-containing solution, adding alkali liquor, calcining, and grinding the calcined product to obtain active metakaolin; and (2) uniformly mixing the waste incineration fly ash with phosphoric acid, drying, uniformly mixing with alkali liquor, and drying again to obtain the active fly ash. And (3) uniformly mixing the active metakaolin with dead burned magnesium oxide powder and fly ash to form an alkaline component. The phosphate, the retarder and the active fly ash are uniformly mixed to form an acidic component. And (4) uniformly mixing the magnesium phosphate cement-based material containing the alkaline component and the acidic component with mixing water and the like to obtain the grouting material. The grouting material prepared by the invention has the technical advantages of quick hardening, early strength, excellent anti-permeability performance, good slurry stability, strong toughness and facilitation of avoiding floating of duct pieces, improving the structural performance of a filling layer and guaranteeing the service safety of subsea tunnels.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement-based material preparation, and in particular to a preparation process of magnesium phosphate cement-based synchronous grouting material for a submarine shield tunnel. Background Art

[0002] The shield method has been gradually widely used in the construction of submarine tunnels. During the construction process, synchronous grouting is usually used to ensure that the stratum is effectively controlled and the stable segment structure is maintained. Synchronous grouting is a construction method in which slurry is injected into the gap at the shield tail through the grouting holes reserved at the shield tail. It can fill the annular gap between the segment and the stratum in time. The filling layer formed after the slurry solidifies and hardens, together with the surrounding rock and the segment, maintains the stability of the submarine tunnel and ensures the service safety of the submarine tunnel.

[0003] Traditional synchronous grouting materials are usually inert slurries, which have a long setting time and low early strength of the filling layer formed. They also cause problems such as the floating of the pipe segments due to the segregation of solid components in the slurry, resulting in a reduction in the overall structural strength of the tunnel. In addition, the long setting time will also bring about serious segregation problems, resulting in poor slurry stability. In addition, in the face of the complex service environment of the submarine tunnel, the filling layer formed by the traditional synchronous grouting material is easily eroded by seawater and causes strength loss, which has an adverse impact on the service safety of the submarine tunnel. Summary of the invention

[0004] In view of the above problems, the present invention provides a preparation process of magnesium phosphate cement-based synchronous grouting material for submarine shield tunnels. The grouting material obtained by this process has technical advantages in terms of rapid hardening and early strength, excellent anti-seepage performance, and good slurry stability. Specifically, the technical solution of the present invention is as follows.

[0005] A preparation process of magnesium phosphate cement-based synchronous grouting material for submarine shield tunnels, comprising the following steps:

[0006] (1) Metakaolin and Mg-containing 2+ The solution is mixed evenly, and then an alkali solution is added and mixed evenly. The obtained metakaolin is calcined, and then the calcined product is ground to obtain active metakaolin.

[0007] (2) The waste incineration fly ash is mixed with phosphoric acid and then dried. Then, the pretreated fly ash is mixed with an alkaline solution and then dried again to obtain activated fly ash.

[0008] (3) The active metakaolin is mixed with heavy burned magnesium oxide powder and fly ash to form an alkaline component for later use. Phosphate, retarder and the active fly ash are mixed to form an acidic component for later use.

[0009] (4) Take the following raw materials: magnesium phosphate cement-based material, fine aggregate, fiber, toughening agent, stabilizer, defoamer, water reducer, and mixing water. The magnesium phosphate cement-based material is formed by the alkaline component and the acidic component. Mix the above raw materials evenly to obtain magnesium phosphate cement-based synchronous grouting material.

[0010] Further, in step (1), the metakaolin and Mg-containing 2+ The solid-liquid ratio of the solution is 1g:2-3.5ml. 2+ The mass fraction of the solution is 10-20%. 2+ The solution includes at least one of magnesium sulfate, magnesium nitrate, magnesium acetate, magnesium bicarbonate solution, and the like.

[0011] Furthermore, in step (1), the OH provided by the alkali solution - With the Mg 2+ The molar ratio of is 2.2 to 2.5: 1. Optionally, the alkali solution includes at least one of sodium hydroxide solution, potassium hydroxide solution, ammonia solution, etc.

[0012] Furthermore, in step (1), the calcination temperature is 550-700° C. and the calcination time is 60-70 min.

[0013] Furthermore, in step (1), the fineness of the activated metakaolin is 200-300 mesh.

[0014] Furthermore, in step (2), the solid-liquid ratio of the waste incineration fly ash to the phosphoric acid is 1 g: 1-1.5 ml. Optionally, the mass fraction of the phosphoric acid is 5-15%.

[0015] Furthermore, in step (2), the drying treatment is carried out at a temperature of 70 to 90° C. and for a time of 40 to 50 minutes to reduce the moisture in the waste incineration fly ash.

[0016] Furthermore, in step (2), the solid-liquid ratio of the pretreated fly ash to the alkali solution is 1g:1-2ml, and the mass fraction of the alkali solution is 10-18%. Optionally, the alkali solution includes at least one of potassium hydroxide, potassium bicarbonate, ammonium bicarbonate solution, etc.

[0017] Furthermore, in step (2), the temperature of the secondary drying treatment is 40 to 60° C., and the time is 80 to 110 minutes.

[0018] Furthermore, in step (3), the weight ratio of the activated metakaolin, the dead-burned magnesium oxide powder and the fly ash is 25-40 parts: 60-90 parts: 30-50 parts.

[0019] Furthermore, in step (3), the weight ratio of the phosphate, retarder and active fly ash is 20-45 parts: 4.5-12 parts: 5-15 parts. Optionally, the phosphate includes at least one of potassium dihydrogen phosphate and ammonium dihydrogen phosphate. The retarder includes at least one of boric acid, borax, zinc sulfate and the like.

[0020] Furthermore, in step (4), the mass ratio of the alkaline component to the acidic component is 3 to 5:1.

[0021] Furthermore, in step (4), the stabilizer comprises cellulose, nano-SiO2, triethanolamine and water glass in a mass ratio of 0.1-0.5:1-5:0.1-0.5:0.05-0.5. Optionally, the cellulose comprises at least one of hydroxypropyl methylcellulose, hydroxymethyl cellulose, hydroxypropyl cellulose, etc. The stabilizer can effectively improve the stability of the grouting material of the present invention and alleviate the above-mentioned problem of pipe segment floating.

[0022] Furthermore, in step (4), the proportions of the components in the raw materials are: 150 to 200 parts by weight of magnesium phosphate cement-based material, 50 to 80 parts by weight of fine aggregate, 1 to 5 parts by weight of fiber, 1 to 3 parts by weight of toughening agent, 1 to 10 parts by weight of stabilizer, 0.2 to 1 part by weight of defoaming agent, 3 to 10 parts by weight of water reducing agent, and 40 to 60 parts by weight of mixing water.

[0023] Furthermore, in step (4), the toughening agent includes at least one of ethylene / vinyl acetate copolymer rubber powder (EVA) rubber powder, styrene-butadiene rubber powder, etc.

[0024] Furthermore, in step (4), the fiber comprises at least one of carbon fiber, polyvinyl alcohol fiber, polyethylene fiber, polypropylene fiber, etc. Optionally, the fiber has a length of 2 to 4 mm and a diameter of 5 to 10 μm.

[0025] Compared with the prior art, the present invention has at least the following beneficial effects:

[0026] The synchronous grouting material for reinforcing submarine shield tunnels of the present invention uses magnesium phosphate cement-based materials as the main gelling component, and has the characteristics of fast solidification rate and high early strength of the filling material formed after hardening. At the same time, the organic film formed by the toughening agent not only increases the toughness of the filling material, improves the deformation resistance of the material, but also can improve the water resistance and impermeability of the material, thereby better ensuring the service safety of the submarine tunnel. In addition, the magnesium phosphate cement-based synchronous grouting material of the present invention is also added with a stabilizer formed by the cellulose, nano-SiO2, triethanolamine and water glass, so that the grouting material prepared by the present invention has high stability, avoids the material segregation phenomenon caused by the floating of solid raw materials such as dead-burned magnesium oxide due to their own gravity, thereby avoiding the floating of the pipe segment and improving the structural performance of the filling material. This is because the cellulose and nano-SiO2 in the stabilizer can be attached to the surface of larger particles to play the role of dispersion, lifting and suspension, improving the stability of the grouting material, and preventing the particles from agglomerating and settling. The triethanolamine not only acts as a catalyst to promote the hydration reaction of the cement material, but also helps to improve the uniformity of the material and ensure that the cement material is fully hydrated. The water glass can increase the viscosity of the material and further prevent the solid-liquid stratification phenomenon.

[0027] In addition, the present invention adopts magnesium phosphate cement-based materials formed by mixing the active metakaolin with the alkaline components formed by heavy burned magnesium oxide powder and fly ash and the acidic components formed by phosphate, retarder and active fly ash. The addition of the modified metakaolin and active fly ash can make the structure of the filling material formed after the magnesium phosphate cement-based material hardens more compact, improve the impermeability and mechanical properties, and also realize the resource utilization of waste incineration fly ash. This is because: first, the present invention adopts Mg-containing 2+ The solution and alkali solution are used to treat the metakaolin, thereby forming magnesium hydroxide on the metakaolin particles, which is converted into magnesium oxide after calcination, so that the metakaolin particles are loaded with magnesium oxide to form active metakaolin. At the same time, under the action of the alkaline component provided by the alkali solution and the high-temperature calcination, the inert mineral phase of the metakaolin is depolymerized to form an active structure [AlO4] 5-etc., which can react with the water glass in the stabilizer to form a calcium aluminosilicate hydrate (CASH) gelling component, which helps to better combine the metakaolin particles with other materials and improve the strength of the filling material. In addition, the present invention first pre-treats the waste incineration fly ash with phosphoric acid, thereby converting the heavy metal elements in the fly ash into phosphate for solidification, thereby preventing the heavy metal elements from entering the filling material and dissolving again to pollute the marine environment. Furthermore, the present invention utilizes alkali solution to treat the above-mentioned fly ash, so that the phosphoric acid remaining in the fly ash reacts with the alkali solution to form phosphate loaded on the fly ash to form active fly ash. After using it as the raw material of magnesium phosphate cement-based material, it can undergo hydration reaction with the dead-burned magnesium oxide in the alkaline component and the magnesium oxide on the metakaolin. At the same time, the metakaolin can also utilize its magnesium oxide to undergo hydration reaction with the phosphate in the acidic component, so that the metakaolin and fly ash have the same type of reaction activity as the magnesium phosphate cement hydration reaction, so that the metakaolin and fly ash can not only play the role of compacting the magnesium phosphate cement hydration product, but also can be cemented together with the magnesium phosphate cement hydration product through the gelled hydration product formed by the hydration reaction, thereby improving the strength of the formed filling material. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0029] Figure 1 This is a sample picture of the magnesium phosphate cement-based synchronous grouting material prepared in the following Example 1.

[0030] Figure 2 The following is a compressive strength test diagram of Example 1.

[0031] Figure 3 This is the anti-seepage and erosion resistance test diagram of the following Example 1. DETAILED DESCRIPTION

[0032] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer.

[0033] Unless otherwise defined, all professional and scientific terms used in the present invention have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. If there are no special instructions, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. Now, the technical solution of the present invention is further described in conjunction with the accompanying drawings and specific embodiments of the specification.

[0034] Example 1

[0035] A preparation process of magnesium phosphate cement-based synchronous grouting material for submarine shield tunnels, comprising the following steps:

[0036] (1) Mix metakaolin and 15% magnesium sulfate solution at a solid-liquid ratio of 1g:3ml and stir evenly. - With Mg 2+ The pretreated metakaolin was heated to 650°C for 60 minutes, the calcined product was cooled to room temperature, ground, and then passed through a 300-mesh sieve to obtain active metakaolin for later use.

[0037] (2) The waste incineration fly ash was mixed with 10% phosphoric acid at a solid-liquid ratio of 1g:1.5ml, and then allowed to stand for 20min, and then dried at 80°C for 45min to obtain pretreated fly ash. The pretreated fly ash was mixed with 15% potassium hydroxide solution at a ratio of 1g:2ml, stirred evenly, and then dried at 50°C for 90min to obtain activated fly ash for later use.

[0038] (3) The active metakaolin prepared in this example is mixed with dead-burned magnesium oxide powder and fly ash in a ratio of 30 parts by weight: 80 parts by weight: 40 parts by weight to form an alkaline component for later use.

[0039] (4) Potassium dihydrogen phosphate, borax and the activated fly ash prepared in this example are mixed in a ratio of 40 parts by weight: 10 parts by weight: 10 parts by weight to form an acidic component. The alkaline component and the acidic component are mixed in a mass ratio of 4:1 and stirred to obtain a magnesium phosphate cement-based material for later use.

[0040] (5) Mix hydroxypropyl methylcellulose, nano-SiO2, triethanolamine and water glass in a mass ratio of 0.2:3:0.35:0.25 and stir evenly to form a stabilizer for later use.

[0041] (6) The following raw materials are taken in parts by weight: 180 parts of the magnesium phosphate cement-based material prepared in this example, 70 parts of 50-mesh machine-made sand fine aggregate, 3 parts of carbon fiber (length 3 mm, diameter 10 μm), 2 parts of toughening agent (ethylene / vinyl acetate copolymer rubber powder (EVA), model 5010N, purchased from Wacker Chemical (China) Co., Ltd.), 6 parts of stabilizer, 0.8 parts of defoaming agent (tributyl phosphate, purchased from Chengdu Clone Chemical Reagent Factory), 7 parts of polycarboxylic acid water reducer, and 50 parts of mixing water.

[0042] (7) First, the magnesium phosphate cement-based material, machine-made sand fine aggregate, fiber, and toughening agent are stirred for 3 minutes, and then the stabilizer is added and stirred for 2 minutes. After completion, the defoamer, water reducer, and mixing water are added and stirred for 2 minutes to obtain the magnesium phosphate cement-based synchronous grouting material.

[0043] Performance Test:

[0044] 1. The stability of the magnesium phosphate cement-based synchronous grouting material prepared in this embodiment is tested. The specific method is as follows: if there is no water precipitation before the grouting material hardens, and the color of the side of the test piece is uniform, it is defined as "good stability". If there is no water precipitation before the grouting material hardens, and the bottom and top of the test piece are uneven in color, it is defined as "good stability". If there is water precipitation before the grouting material hardens, it is defined as "poor stability".

[0045] 2. The magnesium phosphate cement-based synchronous grouting material prepared in this embodiment is poured into a mold to form a mold, and then the molded specimen is demoulded and naturally cured for 1 day. Then, according to the "Test Method for Cement Mortar Strength (ISO Method)" (GB / T17671-2021), a universal press is used to test the 1d compressive strength of the obtained specimen (such as Figure 2 shown).

[0046] 3. The anti-seepage and anti-corrosion properties of the test pieces prepared by the magnesium phosphate cement-based synchronous grouting material prepared in this embodiment are tested. The specific method is: the test pieces of the same batch prepared by the above method are placed in artificially prepared simulated seawater (the configuration of the simulated seawater refers to Alexander.A, that is, each 1L of water contains 24.53g of NaCl, 5.20g of MgCl2, 4.09g of Na2SO4, and 1.16g of CaCl2) and immersed (as shown in Figure 2). Figure 3 The compressive strength of the specimen was tested after 3 days of immersion in seawater. The strength retention rate is the ratio of the compressive strength of the specimen after immersion in seawater to the 1d compressive strength. The higher the compressive strength and strength retention rate after immersion in seawater, the stronger the anti-seepage and anti-corrosion performance of the magnesium phosphate cement-based synchronous grouting material. The test results of the above performance indicators are shown in the following table.

[0047] Performance Indicators stability 1d compressive strength Compressive strength after seawater immersion Strength retention Example 1 good 23.7MPa 22.8MPa 96.20%

[0048] Example 2

[0049] A preparation process of magnesium phosphate cement-based synchronous grouting material for submarine shield tunnels, comprising the following steps:

[0050] (1) Mix metakaolin and 20% magnesium nitrate solution at a solid-liquid ratio of 1g:2ml and stir evenly. - With Mg 2+ The pretreated metakaolin is heated to 550°C for 70 minutes, the calcined product is cooled to room temperature, ground, and then passed through a 200-mesh sieve to obtain active metakaolin for later use.

[0051] (2) The waste incineration fly ash was mixed with 15% phosphoric acid at a solid-liquid ratio of 1g:1.0ml, and then allowed to stand for 20 minutes, and then dried at 70°C for 50 minutes to obtain pretreated fly ash. The pretreated fly ash was mixed with 18% ammonium bicarbonate solution at a ratio of 1g:1.0ml, stirred evenly, and then dried at 40°C for 110 minutes to obtain activated fly ash for later use.

[0052] (3) The active metakaolin prepared in this example is mixed with dead-burned magnesium oxide powder and fly ash in a ratio of 25 parts by weight: 60 parts by weight: 30 parts by weight to form an alkaline component for later use.

[0053] (4) Ammonium dihydrogen phosphate, boric acid and the activated fly ash prepared in this example are mixed in a ratio of 20 parts by weight: 4.5 parts by weight: 5 parts by weight to form an acidic component. The alkaline component and the acidic component are mixed in a mass ratio of 3:1 and stirred to obtain a magnesium phosphate cement-based material for later use.

[0054] (5) Mix hydroxymethyl cellulose, nano-SiO2, triethanolamine and water glass in a mass ratio of 0.1:1:0.1:0.05 and stir evenly to form a stabilizer for later use.

[0055] (6) Take the following raw materials in parts by weight: 150 parts of the magnesium phosphate cement-based material prepared in this example, 50 parts of 80-mesh machine-made sand fine aggregate, 1 part of polyvinyl alcohol fiber (length 4 mm, diameter 10 μm), 1 part of toughening agent (styrene-butadiene rubber powder, purchased from Wacker Chemical (China) Co., Ltd.), 1 part of stabilizer, 0.2 parts of defoaming agent (tributyl phosphate, purchased from Chengdu Clone Chemical Reagent Factory), 3 parts of polycarboxylic acid water reducer, and 40 parts of mixing water.

[0056] (7) First, the magnesium phosphate cement-based material, machine-made sand fine aggregate, fiber, and toughening agent are stirred for 2 minutes, and then the stabilizer is added and stirred for 1 minute. After completion, the defoamer, water reducer, and mixing water are added and stirred for 2 minutes to obtain the magnesium phosphate cement-based synchronous grouting material.

[0057] The various performance indicators of the magnesium phosphate cement-based synchronous grouting material prepared in this embodiment were tested using the same method as in the above-mentioned embodiment 1, and the results are shown in the following table.

[0058] Performance Indicators stability 1d compressive strength Compressive strength after seawater immersion Strength retention Example 2 good 21.4MPa 20.2MPa 94.39%

[0059] Example 3

[0060] A preparation process of magnesium phosphate cement-based synchronous grouting material for submarine shield tunnels, comprising the following steps:

[0061] (1) Mix metakaolin and 10% magnesium acetate solution at a solid-liquid ratio of 1g:3.5ml and stir evenly. - With Mg 2+ Ammonia water is added in a molar ratio of 2.2:1 and stirred evenly to obtain pretreated metakaolin. The pretreated metakaolin is heated to 700°C and kept warm for 60 minutes. The calcined product is cooled to room temperature and ground, and then passed through a 250-mesh sieve to obtain active metakaolin for later use.

[0062] (2) The waste incineration fly ash was mixed with 5% phosphoric acid at a solid-liquid ratio of 1g:1.5ml, and then allowed to stand for 20min, and then dried at 90°C for 40min to obtain pretreated fly ash. The pretreated fly ash was mixed with 10% potassium bicarbonate solution at a ratio of 1g:2.0ml, stirred evenly, and then dried at 60°C for 80min to obtain activated fly ash for later use.

[0063] (3) The active metakaolin prepared in this example is mixed with dead-burned magnesium oxide powder and fly ash in a ratio of 45 parts by weight: 90 parts by weight: 50 parts by weight to form an alkaline component for later use.

[0064] (4) Ammonium dihydrogen phosphate, zinc sulfate and the activated fly ash prepared in this example are mixed in a ratio of 45 parts by weight: 12 parts by weight: 15 parts by weight to form an acidic component. The alkaline component and the acidic component are mixed in a mass ratio of 5:1 and stirred to obtain a magnesium phosphate cement-based material for later use.

[0065] (5) Mix hydroxypropyl cellulose, nano-SiO2, triethanolamine and water glass in a mass ratio of 0.5:5:0.5:0.5 and stir evenly to form a stabilizer for later use.

[0066] (6) Take the following raw materials in parts by weight: 200 parts of the magnesium phosphate cement-based material prepared in this example, 80 parts of 40-mesh machine-made sand fine aggregate, 5 parts of polyethylene fiber (length 2 mm, diameter 5 μm), 3 parts of toughening agent (composed of EVA rubber powder and styrene-butadiene rubber powder in a mass ratio of 1:3, the rubber powder was purchased from Wacker Chemical (China) Co., Ltd.), 10 parts of stabilizer, 1 part of defoaming agent (tributyl phosphate, purchased from Chengdu Clone Chemical Reagent Factory), 10 parts of polycarboxylic acid water reducer, and 60 parts of mixing water.

[0067] (7) First, the magnesium phosphate cement-based material, machine-made sand fine aggregate, fiber, and toughening agent are stirred for 3 minutes, and then the stabilizer is added and stirred for 2 minutes. After completion, the defoamer, water reducer, and mixing water are added and stirred for 2 minutes to obtain the magnesium phosphate cement-based synchronous grouting material.

[0068] The various performance indicators of the magnesium phosphate cement-based synchronous grouting material prepared in this embodiment were tested using the same method as in the above-mentioned embodiment 1, and the results are shown in the following table.

[0069] Performance Indicators stability 1d compressive strength Compressive strength after seawater immersion Strength retention Example 3 good 22.1MPa 21.4MPa 96.83%

[0070] Example 4

[0071] A preparation process of a magnesium phosphate cement-based synchronous grouting material for a submarine shield tunnel is the same as that of the above-mentioned embodiment 1, except that the magnesium phosphate cement-based material of this embodiment is prepared by the following method:

[0072] (1) Mix metakaolin and 15% magnesium sulfate solution at a solid-liquid ratio of 1 g:3 ml and stir evenly to obtain pretreated metakaolin. Heat the pretreated metakaolin to 650° C. and keep the temperature for 60 min. Cool the calcined product to room temperature and grind it. Then pass it through a 300-mesh sieve to obtain active metakaolin for later use.

[0073] (2) The active metakaolin prepared in this example is mixed with dead-burned magnesium oxide powder and fly ash in a ratio of 30 parts by weight: 80 parts by weight: 40 parts by weight to form an alkaline component for later use.

[0074] (3) The alkaline component prepared in this example and the acidic component prepared in the above example 1 are mixed in a mass ratio of 4:1 and stirred evenly to obtain a magnesium phosphate cement-based material.

[0075] The various performance indicators of the magnesium phosphate cement-based synchronous grouting material prepared in this embodiment were tested using the same method as in the above-mentioned embodiment 1, and the results are shown in the following table.

[0076] Performance Indicators stability 1d compressive strength Compressive strength after seawater immersion Strength retention Example 4 good 16.6MPa 14.2MPa 85.54%

[0077] Example 5

[0078] A preparation process of magnesium phosphate cement-based synchronous grouting material for submarine shield tunnels, comprising the following steps:

[0079] (1) The following raw materials were taken in parts by weight: 180 parts of the magnesium phosphate cement-based material prepared in Example 1 above, 70 parts of 50-mesh machine-made sand fine aggregate, 3 parts of carbon fiber (length 3 mm, diameter 10 μm), 2 parts of toughening agent (ethylene / vinyl acetate copolymer rubber powder (EVA), model 5010N, purchased from Wacker Chemical (China) Co., Ltd.), 0.8 parts of defoaming agent (tributyl phosphate, purchased from Chengdu Clone Chemical Reagent Factory), 7 parts of polycarboxylate water reducer, and 50 parts of mixing water.

[0080] (2) First, the magnesium phosphate cement-based material, machine-made sand fine aggregate, fiber, and toughening agent are stirred for 3 minutes, and then the defoamer, water reducer, and mixing water are added and stirred for 2 minutes to obtain the magnesium phosphate cement-based synchronous grouting material.

[0081] The various performance indicators of the magnesium phosphate cement-based synchronous grouting material prepared in this embodiment were tested using the same method as in the above-mentioned embodiment 1, and the results are shown in the following table.

[0082] Performance Indicators stability 1d compressive strength Compressive strength after seawater immersion Strength retention Example 5 Poor stability 19.4MPa 17.8MPa 91.75%

[0083] Example 6

[0084] A preparation process of a magnesium phosphate cement-based synchronous grouting material for a submarine shield tunnel is the same as that of the above-mentioned embodiment 3, except that the magnesium phosphate cement-based material of this embodiment is prepared by the following method:

[0085] (1) Mix metakaolin and 10% magnesium acetate solution at a solid-liquid ratio of 1g:3.5ml and stir evenly. - With Mg 2+ Ammonia water is added in a molar ratio of 2.2:1 and stirred evenly to obtain pretreated metakaolin. The pretreated metakaolin is heated to 70°C and kept warm for 60 minutes. The obtained product is ground and passed through a 250-mesh sieve to obtain active metakaolin for later use.

[0086] (2) The active metakaolin prepared in this example is mixed with dead-burned magnesium oxide powder and fly ash in a ratio of 45 parts by weight: 90 parts by weight: 50 parts by weight to form an alkaline component for later use.

[0087] (3) The alkaline component prepared in this example and the acidic component prepared in the above example 3 are mixed in a mass ratio of 5:1 and stirred evenly to obtain a magnesium phosphate cement-based material.

[0088] The various performance indicators of the magnesium phosphate cement-based synchronous grouting material prepared in this embodiment were tested using the same method as in the above-mentioned embodiment 1, and the results are shown in the following table.

[0089] Performance Indicators stability 1d compressive strength Compressive strength after seawater immersion Strength retention Example 6 good 17.2MPa 15.3MPa 88.95%

[0090] Example 7

[0091] A preparation process of a magnesium phosphate cement-based synchronous grouting material for a submarine shield tunnel is the same as that of the above-mentioned embodiment 2, except that the magnesium phosphate cement-based material of this embodiment is prepared by the following method:

[0092] (1) The waste incineration fly ash and 15% by mass phosphoric acid were mixed at a solid-liquid ratio of 1 g:1.0 ml, and then allowed to stand for 20 minutes, and then dried at 70°C for 50 minutes to obtain pretreated fly ash for later use.

[0093] (2) Ammonium dihydrogen phosphate, boric acid and the pretreated fly ash prepared in this example are mixed uniformly in a ratio of 20 parts by weight: 4.5 parts by weight: 5 parts by weight to form an acidic component for later use.

[0094] (3) The alkaline component prepared in the above Example 2 and the acidic component prepared in this example are mixed in a mass ratio of 3:1 and stirred evenly to obtain a magnesium phosphate cement-based material.

[0095] The various performance indicators of the magnesium phosphate cement-based synchronous grouting material prepared in this embodiment were tested using the same method as in the above-mentioned embodiment 1, and the results are shown in the following table.

[0096] Performance Indicators stability 1d compressive strength Compressive strength after seawater immersion Strength retention Example 7 good 15.8MPa 12.9MPa 81.65%

[0097] Example 8

[0098] A preparation process of a magnesium phosphate cement-based synchronous grouting material for a submarine shield tunnel is the same as that of the above-mentioned embodiment 3, except that the magnesium phosphate cement-based material of this embodiment is prepared by the following method:

[0099] (1) The waste incineration fly ash was mixed with 5% sulfuric acid at a solid-liquid ratio of 1g:1.5ml, and then allowed to stand for 20min, and then dried at 90℃ for 40min to obtain pretreated fly ash. The pretreated fly ash was mixed with 10% potassium bicarbonate solution at a ratio of 1g:2.0ml, stirred evenly, and then dried at 60℃ for 80min to obtain activated fly ash for later use.

[0100] (2) Ammonium dihydrogen phosphate, zinc sulfate and the activated fly ash prepared in this example are mixed in a ratio of 45 parts by weight: 12 parts by weight: 15 parts by weight to form an acidic component. The alkaline component prepared in the above Example 3 and the acidic component prepared in this example are mixed in a mass ratio of 5:1 and stirred to obtain a magnesium phosphate cement-based material.

[0101] The various performance indicators of the magnesium phosphate cement-based synchronous grouting material prepared in this embodiment were tested using the same method as in the above-mentioned embodiment 1, and the results are shown in the following table.

[0102] Performance Indicators stability 1d compressive strength Compressive strength after seawater immersion Strength retention Example 8 good 16.3MPa 14.1MPa 86.50%

[0103] It can be seen from the test results of the above embodiments that, compared with other embodiments, the magnesium phosphate cement-based synchronous grouting materials prepared in Embodiment 1, Embodiment 2 and Embodiment 3 have better early strength, stability and waterproof and erosion resistance, thereby being able to better improve the safety of submarine tunnel service.

[0104] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A preparation process of magnesium phosphate cement-based synchronous grouting material for submarine shield tunnels, characterized in that: The steps include: (1) Metakaolin and Mg-containing 2+ The solution is mixed evenly, and then an alkali solution is added and mixed evenly; the obtained metakaolin is calcined, and then the calcined product is ground to obtain active metakaolin; (2) mixing the waste incineration fly ash and phosphoric acid and then drying them, then mixing the obtained pre-treated fly ash and alkali solution and drying them again to obtain activated fly ash; (3) the activated metakaolin is mixed with heavy-burned magnesium oxide powder and fly ash to form an alkaline component for later use; phosphate, retarder and the activated fly ash are mixed to form an acidic component for later use; (4) taking the following raw materials: magnesium phosphate cement-based material, fine aggregate, fiber, toughening agent, stabilizer, defoamer, water reducer, and mixing water, wherein the magnesium phosphate cement-based material is formed by the alkaline component and the acidic component; and mixing the above raw materials evenly to obtain a magnesium phosphate cement-based synchronous grouting material.

2. The preparation process of magnesium phosphate cement-based synchronous grouting material for submarine shield tunnel according to claim 1, characterized in that: In step (1), the metakaolin and Mg-containing 2+ The solid-liquid ratio of the solution is 1g:2-3.5ml; the Mg-containing 2+ The mass fraction of the solution is 10-20%; Alternatively, the Mg-containing 2+ The solution includes at least one of magnesium sulfate, magnesium nitrate, magnesium acetate and magnesium bicarbonate solution.

3. The preparation process of magnesium phosphate cement-based synchronous grouting material for submarine shield tunnel according to claim 1, characterized in that: In step (1), the alkali solution provides OH - With the Mg 2+ The molar ratio is 2.2 to 2.5:1; Alternatively, the alkali solution includes at least one of sodium hydroxide solution, potassium hydroxide solution, and ammonia water; Alternatively, in step (1), the calcination temperature is 550-700° C. and the calcination time is 60-70 min; Alternatively, in step (1), the fineness of the activated metakaolin is 200-300 mesh.

4. The preparation process of magnesium phosphate cement-based synchronous grouting material for submarine shield tunnel according to claim 1, characterized in that: In step (2), the solid-liquid ratio of the waste incineration fly ash to the phosphoric acid is 1g:1-1.5ml, and the mass fraction of the phosphoric acid is 5-15%; Alternatively, in step (2), the drying treatment is carried out at a temperature of 70 to 90° C. and for a time of 40 to 50 minutes.

5. The preparation process of magnesium phosphate cement-based synchronous grouting material for submarine shield tunnel according to claim 1, characterized in that: In step (2), the solid-liquid ratio of the pretreated fly ash to the alkali solution is 1 g: 1-2 ml, and the mass fraction of the alkali solution is 10-18%; Alternatively, the alkali solution includes at least one of potassium hydroxide, potassium bicarbonate, and ammonium bicarbonate solution; Alternatively, in step (2), the temperature of the secondary drying treatment is 40 to 60° C. and the time is 80 to 110 minutes.

6. The preparation process of magnesium phosphate cement-based synchronous grouting material for submarine shield tunnel according to claim 1, characterized in that: The weight ratio of the active metakaolin, dead-burned magnesium oxide powder and fly ash is 25-40 parts: 60-90 parts: 30-50 parts.

7. The preparation process of magnesium phosphate cement-based synchronous grouting material for submarine shield tunnel according to claim 1, characterized in that: In step (3), the weight ratio of the phosphate, retarder and activated fly ash is 20-45 parts: 4.5-12 parts: 5-15 parts; Alternatively, in step (3), the phosphate includes at least one of potassium dihydrogen phosphate and ammonium dihydrogen phosphate; Alternatively, in step (3), the retarder includes at least one of boric acid, borax and zinc sulfate.

8. The preparation process of magnesium phosphate cement-based synchronous grouting material for submarine shield tunnel according to claim 1, characterized in that: In step (4), the mass ratio of the alkaline component to the acidic component is 3 to 5:

1.

9. The preparation process of magnesium phosphate cement-based synchronous grouting material for submarine shield tunnel according to claim 1, characterized in that: In step (4), the stabilizer comprises cellulose, nano-SiO2, triethanolamine and water glass in a mass ratio of 0.1-0.5:1-5:0.1-0.5:0.05-0.5; Alternatively, the cellulose includes at least one of hydroxypropyl methylcellulose, hydroxymethyl cellulose, and hydroxypropyl cellulose.

10. The process for preparing magnesium phosphate cement-based synchronous grouting material for submarine shield tunnel according to any one of claims 1 to 9, characterized in that: In step (4), the proportions of the components in the raw materials are: 150-200 parts by weight of magnesium phosphate cement-based material, 50-80 parts by weight of fine aggregate, 1-5 parts by weight of fiber, 1-3 parts by weight of toughening agent, 1-10 parts by weight of stabilizer, 0.2-1 parts by weight of defoamer, 3-10 parts by weight of water reducer, and 40-60 parts by weight of mixing water; Alternatively, in step (4), the toughening agent includes at least one of ethylene / vinyl acetate copolymer rubber powder and styrene-butadiene rubber powder; Alternatively, in step (4), the fiber comprises at least one of carbon fiber, polyvinyl alcohol fiber, polyethylene fiber, and polypropylene fiber; Alternatively, in step (4), the fiber has a length of 2 to 4 mm and a diameter of 5 to 10 μm.

Citation Information

Patent Citations

  • Preparation method of metakaolin-based magnesium oxide type rapid repair material

    CN104402392A

  • Ground surface course based on phosphorus and magnesium material and construction process thereof

    CN108947464A

  • Method for preparing rapid pavement repairing material from waste incineration fly ash

    CN110615660A

  • Alkaline aluminoferrosilicate hydraulic cement

    EP0895972A1

  • Phospholipid composition containing surfactant and use thereof

    KR1020250068324A